Nonbank lenders as global shock absorbers: Evidence from US Monetary Policy spillovers - David Elliott; Ralf R. Meisenzahl; José-Luis Peydró (Federal Reserve Bank of Chicago, 2023)
We show that nonbank lenders act as global shock absorbers from US monetary policy spillovers. We exploit loan-level data from the global syndicated lending market and US monetary policy surprises. When US policy tightens, nonbanks increase dollar credit supply to non-US firms (relative to banks), mitigating the dollar credit reduction. This increase is stronger for riskier firms, proxied by emerging market firms, high-yield firms, or firms in countries with stronger capital inflow restrictions. However, firm-lender matching, zombie lending, fragile-nonbank lending, or periods of low vs higher local GDP growth do not drive these results. Furthermore, the substitution from bank to nonbank credit has firm-level real effects. Consistent with a funding-based mechanism, when US monetary policy tightens, non-US nonbanks increase short-term dollar debt funding, relative to banks. In sum, despite increased risk-taking by less regulated and more fragile nonbanks (relative to banks), access to nonbank credit reduces the volatility in capital flows-and associated economic activity-stemming from US monetary policy spillovers, with important implications for theory and policy.
Keywords: E5; F34; F42; G21; G23; G28; 330; Nonbank lending; International monetary policy spillovers; Global financial cycle; Banks; US dollar funding for non-US firms